Optimal protamine-to-heparin dosing ratio for the prevention of bleeding complications in patients undergoing TAVR – a multicentre experience. (3rd October 2022) - Al-Kassou, B; Veulemans, V; Shamekhi, J; Maier, O; Aksoy, A; Zietzer, A; Meertens, M; Weber, M; Sinning, J M; Adam, M; Zimmer, S; Baldus, S; et al.
Abstract: Background: Despite major advances, transcatheter aortic valve replacement (TAVR) is associated with procedure-related vascular and bleeding complications, that have a significant impact on mortality. A recently published study has shown that heparin antagonization using protamine resulted in significantly lower rates of serious bleeding events in patients undergoing TAVR as compared to those without heparin reversal. However, the optimal protamine-to-heparin dosing ratio to prevent bleeding complications without increasing ischemic complications in patients undergoing TAVR is unknown. Accordingly, daily clinical practice varies between selective to routine administration of protamine in different dosing ratios. Purpose: The aim of this observational multicentre study was to compare the safety and efficacy of two different protamine-to-heparin dosing ratios for the prevention of bleeding complications after TAVR. Methods: The study included 1446 patients undergoing TAVR, of whom 623 (43.1%) received partial and 823 (56.9%) full heparin antagonization (0.4–0.6 mg versus 0.9–1.0 mg protamine/100 units of heparin). The indication for partial or full heparin antagonization was left to the discretion of the operator, who made the decision according to the patient's individual thrombotic and bleeding risk. The primary endpoint was a composite of 30-day mortality, life-threatening and major bleeding. Safety endpoints included stroke and myocardial infarction at 30 days. Results: The overall study population had a mean age of 81.1±6.0 years; 47.9% were of female gender. The baseline characteristics were well balanced between the two groups. Full antagonization of heparin resulted in significantly lower rates of the primary endpoint as compared to partial heparin reversal (5.6 vs. 10.4%, p<0.01), mainly driven by lower rates of life-threatening (0.5 vs 1.6%, p=0.05) and major bleeding (3.2 vs 7.5%, p<0.01). The incidence of major vascular complications was significantly lower in patients with full heparin reversal (3.5 vs 7.5%, p<0.01), as presented in Figure 1. Accordingly, the post-interventional drop in hemoglobin level and the need for red-blood-cell transfusion was lower in patients receiving full as compared to partial heparin reversal (1.5±1.2 vs 1.7±1.2 g/dl, p<0.01; 10.4 vs 15.9%, p<0.01, respectively). Regarding safety endpoints, no differences were observed in the incidence of stroke and myocardial infarction between the groups (2.2 vs 2.6%, p=0.73 and 0.2 vs 0.4%, p=0.64, respectively). Multivariate regression analyses revealed that full antagonization of heparin (OR: 0.43 [95% CI: 0.24–0.81], p<0.01) was independently associated with the primary end point Conclusion: Full heparin antagonization resulted in significantly lower rates of life-threatening and major bleeding after TAVR as compared to partial heparin reversal. The occurrence of stroke and myocardial infarction was low and comparable between both groups. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation).